Existence of a solution of the quasivariational inequality with semicontinuous operator - Jovanov, D.S. (Yugoslav Journal of Operations Research; Vol 16 No 2 (2006): Vol. 16 No. 2, 2016)
The paper considers quasi-variational inequalities with point to set operator. The existence of a solution, in the case when the operator of the quasi-variational inequality is semi-continuous and the feasible set is convex and compact, is proved.